2011
DOI: 10.1038/gt.2011.123
|View full text |Cite
|
Sign up to set email alerts
|

The combination of chemotherapy with HVJ-E containing Rad51 siRNA elicited diverse anti-tumor effects and synergistically suppressed melanoma

Abstract: Dacarbazine (DTIC) is one of the most popular alkylating agents used for the treatment of malignant melanoma. DTIC induces apoptosis of melanoma cells via double-strand breaks (DSBs). Melanoma cells, however, tend to increase their expression of DNA repair molecules in order to be resistant to DTIC. Here, we show that DTIC increases expression of Rad51, but not Ku70, in a cultured B16-F10 mouse melanoma cell line in dose-and time-dependent manners. On introducing Rad51 short interfering RNA (siRNA) with the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…The decrease of RAD51 expression may induce non-effective homologous recombination repair, resulting in mitotic catastrophe or apoptosis. [34][35][36] Hence, we explored the role of miR-708 in cisplatin treatment and found that miR-708 potentiates cisplatin efficacy in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of RAD51 expression may induce non-effective homologous recombination repair, resulting in mitotic catastrophe or apoptosis. [34][35][36] Hence, we explored the role of miR-708 in cisplatin treatment and found that miR-708 potentiates cisplatin efficacy in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, structural changes in this domain will consequently influence the conformational flexibility of the CAT domain. Additional studies are required to elucidate the structural consequences of the decreased side-chain flexibility of the D-loop residues, such as Tyr889, on PARP trapping [ 215 ].…”
Section: The Poly(adp) Ribose Polymerasementioning
confidence: 99%
“…Because cells cannot circumvent even one unrepaired DSB, inactivation of RAD51 is expected to increase cell sensitivity to DNA damage [19]. Indeed, down-regulation of RAD51 by siRNA was successfully used to sensitize HeLa cells to cisplatin [20], [21].…”
Section: Introductionmentioning
confidence: 99%